Community Readiness for an Aging Society in Semi-Rural and Rural Communities of Trang Province, Southern Thailand: A Mixed-Methods Approach - Damkhong, Suthee; Akkarasuwannakul, Anan; Raksanam, Buppha; Tubthieng, Wanipa; Raham, Pattarawadee (Journal of Cultural Analysis and Social Change, 2025)
This mixed-methods study investigates community readiness for supporting an aging society in Trang Province, Southern Thailand, across five dimensions: health, economy, society, environment, and technology. Conducted in two phases—(1) assessing community preparedness and (2) developing context-sensitive policy recommendations—the study involved 697 participants from urban, semi-urban, and rural areas using surveys, in-depth interviews, focus groups, and participant observation. Quantitative data were analyzed with descriptive statistics and one-way ANOVA, while qualitative data were examined thematically. Findings indicate moderate to high community readiness, yet structural and cultural challenges persist. Economic vulnerability is pronounced, with 51.9% of households reporting unstable income and 56.2% indicating debt. Common health issues include hypertension, diabetes, and osteoarthritis. Environmental limitations, such as 34.1% of households continuing to use squat toilets, highlight infrastructural gaps. Social support and engagement remain strong but vary significantly across subdistricts (p < 0.05). Based on these results, a five-dimensional policy framework is proposed, integrating preventive health care, economic security, social participation, age-friendly infrastructure, and digital inclusion. Lifelong learning and participatory governance are emphasized as key strategies for empowering older adults. Comparative analysis underscores the importance of social capital, cultural norms, and multi-sectoral collaboration in achieving equitable aging policies. Strengthening cross-level coordination and community ownership is essential for transforming readiness into long-term resilience and improving quality of life for older adults.